IBM DS8000 easy tier (for DS8880 R8.5) - Dufrasne, Bertrand; Kimmel, Peter; Houzenga, Matthew; Robertson, Dennis (IBM redpaper., 2018)
This IBM® Redpaper"!publication describes the concepts and functions of IBM System Storage® Easy Tier®, and explains its practical use with the IBM DS8000® series and License Machine Code 7.9.0.xxx (also known as R9.0). Easy Tier is designed to automate data placement throughout the storage system disks pool. It enables the system to (automatically and without disruption to applications) relocate data (at the extent level) across up to three drive tiers. The process is fully automated. Easy Tier also automatically rebalances extents among ranks within the same tier, removing workload skew between ranks, even within homogeneous and single-tier extent pools. Easy Tier supports a Manual Mode that enables you to relocate full volumes. Manual Mode also enables you to merge extent pools and offers a rank depopulation function. Easy Tier fully supports thin-provisioned Extent Space Efficient fixed block (FB) and count key data (CKD) volumes in Manual Mode and Automatic Mode. Easy Tier also supports extent pools with small extents (16 MiB extents for FB pools and 21 cylinders extents for CKD pools). Easy Tier also supports high-performance and high-capacity flash drives in the High-performance flash enclosure, and it enables additional user controls at the pool and volume levels. This paper is aimed at those professionals who want to understand the Easy Tier concept and its underlying design. It also provides guidance and practical illustrations for users who want to use the Easy Tier Manual Mode capabilities. Easy Tier includes additional capabilities to further enhance your storage performance automatically: Easy Tier Application, and Easy Tier Heat Map Transfer